The Phase II Murchison Widefield Array: Design overview. (23rd November 2018) - Wayth, Randall B.; Tingay, Steven J.; Trott, Cathryn M.; Emrich, David; Johnston-Hollitt, Melanie; McKinley, Ben; Gaensler, B. M.; Beardsley, A. P.; Booler, T.; Crosse, B.; Franzen, T. M. O.; Horsley, L.; et al.
Abstract: We describe the motivation and design details of the 'Phase II' upgrade of the Murchison Widefield Array radio telescope. The expansion doubles to 256 the number of antenna tiles deployed in the array. The new antenna tiles enhance the capabilities of the Murchison Widefield Array in several key science areas. Seventy-two of the new tiles are deployed in a regular configuration near the existing array core. These new tiles enhance the surface brightness sensitivity of the array and will improve the ability of the Murchison Widefield Array to estimate the slope of the Epoch of Reionisation power spectrum by a factor of ∼3.5. The remaining 56 tiles are deployed on long baselines, doubling the maximum baseline of the array and improving the array u, v coverage. The improved imaging capabilities will provide an order of magnitude improvement in the noise floor of Murchison Widefield Array continuum images. The upgrade retains all of the features that have underpinned the Murchison Widefield Array's success (large field of view, snapshot image quality, and pointing agility) and boosts the scientific potential with enhanced imaging capabilities and by enabling new calibration strategies.